Assessment of satisfaction in emergency remote learning from pharmacy students’ perspective in a public university in Brazil (Research, Society and Development, 2024)
The remote teaching-learning process in the Baccalaureate of Pharmacy at UFMG brought many challenges to the students, thus our objective was to assess the satisfaction of the students with the ERL. It was evaluated when the classes were instituted by means of Emergency Remote Learning (ERL), during the coronavirus pandemic (SARS-CoV-2). A questionnaire addressing teaching-learning data, sociodemographic habits and lifestyle was collected through a virtual platform and, data are analyzed by linear regression and by the Classification And Regression Tree (CART) technique. The overall mean students´ satisfaction with ERL was 3.12±1.10 (Likert scale 1-5), presenting an inverse correlation with learning in the professional cycle of the course (p